Interface shear strength properties of geogrid-reinforced steel slags using a large-scale direct shear testing apparatus. Issue 5 (October 2020) - Maghool, Farshid; Arulrajah, Arul; Mirzababaei, Mehdi; Suksiripattanapong, Cherdsak; Horpibulsuk, Suksun
Abstract: This research evaluates the shear strength properties of unreinforced and geogrid-reinforced ladle furnace slag (LFS), electric arc furnace slag (EAFS) and a blend comprising 50% LFS and 50% EAFS (LFS50+EAFS50) using the large direct shear testing apparatus (DST). The large DST results of unreinforced steel slags indicated that LFS had the lowest shear stress ratio at the peak shear strength among all samples, while LFS50+EAFS50 samples (both unreinforced and reinforced) demonstrated the highest shear stress ratio amongst the tested samples. A higher apparent cohesion value was achieved with the inclusion of biaxial geogrid in LFS and EAFS samples as compared to the triaxial geogrid interface. The observed behavior can be attributed to the larger aperture size of the biaxial geogrid compared to the triaxial geogrid leaving more void planar space for a direct interaction between slag particles. In contrast, the apparent cohesion of LFS50+EAFS50 without a geogrid interface was high and did not change significantly with the insertion of geogrid. Given, the range of internal friction angles for ordinary soils, studied slag by-products achieved internal friction angles in excess of 59° (with no geogrid interface) and these significant values proved highly beneficial application for these waste materials in pavement construction. Highlights: Large scale direct shear tests on geogrid-reinforced LFS and EAFS blends. Biaxial geogrid provides higher interface strength than the triaxial geogrid. Beneficial application of such waste materials in pavement construction is proved.